Child Abuse & Neglect: An Overview (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Child abuse has been recognized as a global phenomenon. It has detrimental consequences on all the aspects of child development. Solving this universal problem, requires better understanding of its occurrence in varied range of settings, as well as of its causes and consequences in these settings The majority of preventive programs focus on victims or perpetrators of child abuse and neglect. Very few programs emphasize on primary preventive approach aimed at preventing the child abuse & neglect from taking place at the initial stage. Effort must be made to prevent child abuse and neglect from occurring at all. This article provides an overview of child abuse and neglect at global level.
Keywords: Child Abuse; Child Maltreatment; Neglect.